RARE EARTH ELEMENTS IN THE ORES OF EPITHERMAL GOLD-SILVER AND SILVER DEPOSITS, RUSSIA'S NORTHEAST - Kravtsova R.G.; Almaz Ya.A. (My University, 2006)
Relations between mineralization and magmatic rocks and sources of ore-forming fluids are presently among the most important problems in endogenous ore formation. Geochemical methods provide a valuable insight into these problems. The estimation of ore potential and search for reliable criteria for the determination of sources of ore elements are based mainly on the study and comparison of the ore-element compositions of rocks and ores. In this study, we attempted to solve these problems by a nontraditional way, studying REE distribution in ores and comparing it with the behavior of these elements in igneous rocks.